Estudo teórico de clusters bimetálicos de cobre incrementados com átomos de prata - Leite, Francinaldo dos Santos (2017)
The structures Cu3Agn, with n ranging from 3 to 25, using the Genetic Algorithm (GA) methodology and later the most stable structures (Cu3Ag10, Cu3Ag16 and Cu3Ag19) were studied through the Functional Theory of (DFT) density. The DFT calculations were performed with the SIESTA computational package, with the (PBE / DZP) theory level. In addition, we performed calculations in the Gaussian 09 computational package to verify the fundamental state, as well as to obtain spectroscopic data, where we analyzed PDOS, spin multiplicity and infrared. The results showed that the Cu orbital of the Cu most contributed to form the bond and to the atom of Ag 4p. The lowest energy values in the multiplicities sexteto, dubleto and quarteto, were found respectively for the Cu3Ag10, Cu3Ag16 and Cu3Ag20 clusters. Infrared data revealed that the Cu-Cu bonds showed a wavelength equal to 80 cm -1, Cu-Ag at 160 cm -1 and Ag-Ag at 180 cm -1. Therefore, it is concluded that the electronic and magnetic effects are influenced by the size and omposition of the clusters and that in the proportion Ag is added the gap obtained through HOMO-LUMO tends to decrease.